2023
DOI: 10.1039/d3ay01219k
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman spectroscopy hair analysis after household contamination

Abstract: Trace evidence found at crime scenes is rarely in an unsullied condition. It has been demonstrated that surface-enhanced Raman spectroscopy (SERS) can be used for the detection of artificial hair...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The pH of each soil type was measured using a benchtop pH meter to be 6.38, 6.81, and 9.96, for soil types A, B, and C, respectively. In our previous study, we showed that substances with acidic pH, such as white wine and orange juice, drastically lower the accuracy of SERS-based identification of colorants on hair 16 . We hypothesized that the acidic pH facilitates the desorption of artificial colorants from the hair surface.…”
Section: Methodsmentioning
confidence: 97%
“…The pH of each soil type was measured using a benchtop pH meter to be 6.38, 6.81, and 9.96, for soil types A, B, and C, respectively. In our previous study, we showed that substances with acidic pH, such as white wine and orange juice, drastically lower the accuracy of SERS-based identification of colorants on hair 16 . We hypothesized that the acidic pH facilitates the desorption of artificial colorants from the hair surface.…”
Section: Methodsmentioning
confidence: 97%
“…Experimental findings reported by Casadio and co-workers demonstrated that colored fabric often exhibits strong fluorescence, which obscures the possibility of using RS for the identification of both fabric material and dyes [11]. Van Duyne's group demonstrated that noble metal nanostructures could be used to both suppress the fluorescence and enhance the Raman scattering from dye molecules present in fabric [25][26][27]. This analytical approach is known as surface-enhanced Raman spectroscopy (SERS) [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%